The Perfect-Circle Technique Demonstrates Poor Inter-Rater Reliability in Measuring Posterior Glenoid Bone Loss on Magnetic Resonance Imaging - Nata Parnes, M.D; Kyle J. Klahs, D.O; Alexis B. Sandler, M.D; Emily I. Wynkoop, M.D; Adam Goldman, D.O; Keith Fishbeck, D.O; Robert H. Rolf, M.D; John P. Scanaliato, M.D (Elsevier, 2024)
Purpose: To evaluate the reliability of the "perfect-circle" methodology for measurement of glenoid bone loss with magnetic resonance imaging (MRI) in patients with posterior glenohumeral instability. Methods: A prospective chart review was performed on patients who underwent isolated arthroscopic posterior labral repairs in our institution's electronic medical records between January 1, 2021, and June 30, 2021. Inclusion criteria included isolated posterior shoulder instability with posterior labral repair and corroborated tears on MRI. A total of 9 raters, either sports or shoulder and elbow fellowship-trained orthopaedic surgeons, each evaluated the affected shoulder MRI scans twice, at over 2 weeks apart. Measurements followed the "perfect-circle" technique and included projected anterior-to-posterior (AP) glenoid diameter, amount of posterior bone loss, and percentage of posterior bone loss. Results: Ten consecutive patients between the ages of 17 and 46 years with diagnosed posterior glenohumeral instability were selected. The average age was 28 ± 10 years, and 60% of patients were male. The patient's dominant arm was affected in 40%, and 50% of cases involved the right shoulder. The average glenoid diameter was 29.62 ± 3.69 mm, and the average measured bone loss was 2.8 ± 1.74 mm. The average percent posterior glenoid bone loss was 9.41 ± 5.78%. The inter-rater reliability was poor for the AP diameter and for the posterior glenoid bone loss with intraclass correlation coefficients at 0.30 (0.12-0.62) and 0.22 (0.07-0.54) respectively. The intrarater reliability was poor for AP diameter and moderate for posterior glenoid bone loss, with intraclass correlation coefficients at 0.41 (0.22-0.57) and 0.50 (0.33-0.64), respectively. Conclusions: Using the "perfect-circle" technique for evaluating posterior glenohumeral bone loss has poor-to-moderate inter- and intrarater reliability from MRI. Level of Evidence: Level IV, prospective diagnostic study.